Baclofen Protects Primary Rat Retinal Ganglion Cells from Chemical Hypoxia-Induced Apoptosis Through the Akt and PERK Pathways - Fu, Pingping; Wu, Qiang; Hu, Jianyan; Li, Tingting; Gao, Fengjuan (Frontiers in Cellular Neuroscience, 2016)
Retinal ganglion cells (RGCs) consume large quantities of energy to convert light information into a neuronal signal, which makes them highly susceptible to hypoxic injury. This study aimed to investigate the potential protection by baclofen, a GABAB receptor agonist, of retinal ganglion cells against hypoxia-induced apoptosis. CoCl2 was applied to mimic hypoxia. Primary rat retinal ganglion cells (RGCs) were subjected to CoCl2 with or without baclofen treatment, and RNA interference techniques were used to knock down the GABAB2 gene in the primary RGCs. The viability and apoptosis of RGCs were assessed using cell viability and TUNEL assays, Hoechst staining, and flow cytometry. The expression of cleaved caspase-3, bcl-2, bax, Akt, phospho-Akt, PERK, phospho-PERK, eIF2α, phospho-eIF2α, ATF-4, and CHOP were measured using western blotting. GABAB2 mRNA expression was determined using quantitative real-time polymerase chain reaction (qRT-PCR) analysis. Our study revealed that CoCl2 significantly induced RGC apoptosis and that baclofen reversed these effects. CoCl2-induced reduction of Akt activity was also reversed by baclofen. Baclofen prevented the activation of the PERK pathway and the increase in CHOP expression induced by CoCl2. Knockdown of GABAB2 and the inactivation of the Akt pathway by inhibitors reduced the protective effect of baclofen on CoCl2-treated RGCs. Taken together, these results demonstrate that baclofen protects RGCs from CoCl2-induced apoptosis by increasing Akt activity and by suppressing the PERK pathway and CHOP activation.